A Survey on Visual Information Search Behavior and Requirements of Radiologists - Markonis, D.; Holzer, M.; Dungs, S.; Vargas, A.; Langs, G.; Kriewel, S.; Müller, H. (Methods of Information in Medicine, 2012)
Objectives: The main objective of this study is to learn more on the image use and search requirements of radiologists. These requirements will then be taken into account to develop a new search system for images and associated meta data search in the Khresmoi project.Methods: Observations of the radiology workflow, case discussions and a literature review were performed to construct a survey form that was given online and in paper form to radiologists. Eye tracking was performed on a radiology viewing station to analyze typical tasks and to complement the survey.Results: In total 34 radiologists answered the survey online or on paper. Image search was mentioned as a frequent and common task, particularly for finding cases of interest for differential diagnosis. Sources of information besides the Internet are books and discussions with colleagues. Search for images is unsuccessful in around 25% of the cases, stopping the search after around 10 minutes. The most common reason for failure is that target images are considered rare. Important additions for search requested in the survey are filtering by pathology and modality, as well as search for visually similar images and cases. Few radiologists are familiar with visual retrieval but they desire the option to upload images for searching similar ones.Conclusions: Image search is common in radiology but few radiologists are fully aware of visual information retrieval. Taking into account the many unsuccessful searches and time spent for this, a good image search could improve the situation and help in clinical practice.
Keywords: User behavior; survey; image retrieval; radiology